Multiple mobile clots in right atrium and ventricle following insertion of temporary pace maker :A case report - Nabati M; Tabiban S; Moshtaghian Sh; Eslami S (مجله دانشگاه علوم پزشکی گرگان, 2013)
Temporary pace marker (TPM) usually has been used in emergency conditions. Insertion of TPM is accompanied with vein thrombosis and pulmonary Emboli. TPM was inserted via right femoral vein in 73 years male due to complete heart block. Thereafter, he was suffered from deep vein thrombosis. Echocardiography revealed multiple mobile clots in right atrium, ventricle and impending pulmonary thromboemboli following insertion of permanent pacemaker. Despite of contraindication for the application of thrombolytic agents due to surgical incision for permanent pacemaker and presence of patent foramen oval, the patient survived from massive pulmonary thromboemboli and death due to rapid diagnosis and on time treatment with anticoagulation agents without performing surgery.